Experimental and Numerical Investigation of Advanced Materials and Structures - <U+00d6>chsner, Andreas.; Altenbach, Holm. (Advanced Structured Materials,, 2013)
The idea of this monograph is to present the latest results related to experimental and numerical investigations of advanced materials and structures. The contributions cover the field of mechanical, civil and materials engineering, ranging from new modelling and simulation techniques, advanced analysis techniques, optimization of structures and materials and constitutive modelling. Well known experts present their research on damage and fracture of material and structures, materials modelling and evaluation up to image processing and visualization for advanced analyses and evaluation.